Topographic survey of atypical endometrial disorder associated with the presence of chorionic tissue. Demonstration of alteration in the endocervix - Arias Stella, Javier (1956)
In 1954 we made the description and characterization of endometrial epithelial one alteration that occurs in some cases of chorionic, mola hidcrtidiforme, destruens chorioadenoma, cervical ectopic pregnancy and abortion. The alteration is characterized mainly by a nuclear hypertrophy with enlargement to a lesser degree in the cytoplasm and loss trend cell polarization. The affected glands may be secretory or proliferative, or show a pathological secretory and proliferative activity simultaneously. The cover may show epithelial injury. The alteration occurs focally compromising all or part of a gland or glands groups. Rarely is more or less diffuse. It may or not be decidual reaction.